2008
DOI: 10.1002/ptr.2415
|View full text |Cite
|
Sign up to set email alerts
|

An observational study and quantification of the actives in a supplement with Sambucus nigra and Asparagus officinalis used for weight reduction

Abstract: The aim of the study was to obtain information on the content of co-active compounds of a food supplement recommended as a weight reduction diet and on its short-term effectiveness and safety as a starter for lifestyle change. Eighty participants completed the protocol. The Sambucus nigra L. berry juice enriched with flower extract and tablets containing berry powder and flower extract provided a total of 1 mg anthocyanins, 370 mg flavonol glycosides and 150 mg hydroxycinnamates per day; the Asparagus officina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 20 publications
1
23
0
2
Order By: Relevance
“…Multiple studies have demonstrated the antiinflammatory effects of S. nigra (Mascolo et al, 1987;Timoshenko and Cherenkevich, 1995;Yesilada et al, 1997;Haas et al, 1999;Barak et al, 2001;Bobek et al, 2001;Barak et al, 2002;Harokopakis et al, 2006;Thole et al, 2006;Ulbricht et al, 2014). It appears to act as a diuretic (Beaux et al, 1999), and to lower blood pressure (Chrubasik et al, 2008;Hasani-Ranjbar et al, 2009). It may have potential in the reduction of certain genotoxin levels (Cheng et al, 2007) and shows promise in the inhibition of certain cancers (Emig et al, 1995;Thole et al, 2006).…”
Section: General Health Propertiesmentioning
confidence: 99%
“…Multiple studies have demonstrated the antiinflammatory effects of S. nigra (Mascolo et al, 1987;Timoshenko and Cherenkevich, 1995;Yesilada et al, 1997;Haas et al, 1999;Barak et al, 2001;Bobek et al, 2001;Barak et al, 2002;Harokopakis et al, 2006;Thole et al, 2006;Ulbricht et al, 2014). It appears to act as a diuretic (Beaux et al, 1999), and to lower blood pressure (Chrubasik et al, 2008;Hasani-Ranjbar et al, 2009). It may have potential in the reduction of certain genotoxin levels (Cheng et al, 2007) and shows promise in the inhibition of certain cancers (Emig et al, 1995;Thole et al, 2006).…”
Section: General Health Propertiesmentioning
confidence: 99%
“…The anticarcinogenic and antioxidative effect of elderberry juice has also been attributed to the high content of anthocyanins and other flavonoids (Kaack & Austed, 1998). A low-calorie juice cocktail (including elderberry) rich in anthocyanins was successfully used in a weight loss program in obese men (Chrubasik et al, 2008). Furthermore, the con- Composition (%) of the medicinal plants in fatty acids (mean ± SD; n = 9).…”
Section: Compoundmentioning
confidence: 99%
“…Flowers of S. nigra have been found to contain hydroxycinnamic acids, mono-and di-caffeoylquinic acid derivatives, flavones and flavonol glycosides (Christensen, Kaack, & Fretté, 2008;Dawidowicz, Wianowska, Gawdzik, & Smolarz, 2003;Rieger, Müller, Guttenberger, & Bucar, 2008). Elderflower is recommended by the German Commission E for upper respiratory tract infections for its secretolytic effect (Chrubasik et al, 2008). Its pharmacological properties result, among other things, from the presence of flavonoids (Dawidowicz, Wianowska, & Baraniak, 2006).…”
Section: Sambucus Nigramentioning
confidence: 99%
“…Table 1 shows that there was no statistically significant difference in the before and after urine collection, while the patients lost a mean of 2.6 kg body weight. It is assumed that the low quantity of anthocyanins found in the Sambucus concentrate used in the hypocaloric diet (Chrubasik et al, 2008) may account for the lack of effect on pH. Nephrolithiasis is a frequent, multifactorial metabolic disease, with a high rate of recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that juice from Vaccinium macrocarpon due to its urine acidifying effect might be useful in the treatment of brushite and struvite stones, whereas juice from Ribes nigrum L. could support the treatment and metaphylaxis of uric acid stone disease because of its alkalizing effect. A hypocaloric diet based on Sambucus nigra L. and Asparagus officinalis L. was recently employed (Chrubasik et al, 2008). In order to obtain information on the impact of the Sambucus nigra concentrate on the urinary electrolyte balance, the 24 h urine of 11 participants who used solely a proprietary Sambucus concentrate component of the diet was analysed for its pH before and on day 7 of the diet.…”
Section: Introductionmentioning
confidence: 99%